Tainted tap : Flint's journey from crisis to recovery - Davis, Katrinell (University of North Carolina Press, 2021)
"After a cascade of failures left residents of Flint, Michigan, without a reliable and affordable supply of safe drinking water, citizens spent years demanding action from their city and state officials. Complaints from the city's predominantly African American residents were ignored until independent researchers confirmed dangerously elevated blood lead levels among Flint children and in the city's tap water. Despite a 2017 federal court ruling in favor of Flint residents who had demanded mitigation, such efforts have been incomplete at best. Assessing the challenges that community groups faced in their attempts to advocate for improved living conditions, 'Tainted Tap' offers a rich analysis of conditions and constraints that created the Flint water crisis"-- Provided by publisher.
Keywords: Drinking water -- Contamination -- Social aspects -- Michigan -- Flint.; Drinking water -- Lead content -- Michigan -- Flint.; Public health administration -- Michigan -- Flint.; Water quality management -- Michigan -- Flint.; Flint (Mich.) -- Politics and government.; Flint (Mich.) -- Social conditions.; Flint (Mich.) -- Economic conditions.; Eau potable -- Contamination -- Aspect social -- Michigan -- Flint.; Eau potable -- Teneur en plomb -- Michigan -- Flint.; Santé publique -- Administration -- Michigan -- Flint.; Eau -- Qualité -- Gestion -- Michigan -- Flint.; SOCIAL SCIENCE / Ethnic Studies / African American Studies; Drinking water -- Lead content; Economic history; Politics and government; Public health administration; Social conditions; Water quality management; Michigan -- Flint